STUDI KASUS : EARLY WARNING SIGNS PADA KEHAMILAN TRIMESTER AKHIR MELALUI ASUHAN KEBIDANAN 10T - Kotarumalos, Sitti Sarifah; Fasiha, Fasiha (Jurnal Kebidanan, 2025)
Late pregnancy is a critical phase because the risk of complications such as preeclampsia, bleeding, infection, and premature rupture of membranes increases, making early detection of Early Warning Signs (EWS) highly important. This case study aims to describe the implementation of the 10T-based midwifery care approach and its role in early detection in a pregnant woman, Mrs. D, G2P1A0, at 32 weeks of gestation who visited Rijali Health Center for routine antenatal care. Data were collected through interviews, observation, physical examination, and supporting examinations. The assessment showed that the mother and fetus were in good condition without any pregnancy danger signs; complaints of frequent urination and sleep disturbances were physiological discomforts of the third trimester. Blood pressure of 110/70 mmHg, fetal heart rate of 148 bpm, fundal height of 25 cm, and hemoglobin level of 11.8 g/dL indicated a low-risk physiological pregnancy. The application of the 10T components—including physical measurements, laboratory evaluation, management of complaints, iron supplementation, tetanus immunization, counseling on danger signs, and documentation in the maternal health book—proved helpful for midwives in conducting early detection and preventing complications. Education regarding rest patterns, nutrition, and warning signs increased the mother’s preparedness for childbirth. In conclusion, 10T-based midwifery care is effective in maintaining maternal well-being and supporting early detection of obstetric risks in late pregnancy. Pregnant women are advised to attend ANC regularly, consume iron supplements, and understand danger signs, while midwives should continue implementing the 10T components thoroughly and providing comprehensive counseling.